Efforts To Improve Learning Outcomes In The Game Of Passing Football Through Teaching Command Style - Muhammad Deni Kurniawan; Rinaldi Aditya; Agung Nugroho (Jurnal Mahasiswa Pendidikan Olahraga, 2020)
The purpose of this study was to improve student learning outcomes in Physical Education subjects, especially in passing material by using a commando teaching style in grade III SD students. Al Wasliyah Marelan 25. This research method is classroom action research and the research subject is a class that has certain problems. The class studied consisted of 26 students. The instruments used in this study were test results of learning and observation or observation sheets. From the results of the research conducted, it was seen that the increase in the first cycle was 57.69%, then increased to 88.46% in the second cycle. From the data analysis, it can also be seen that the student learning outcomes from the learning outcomes test before using the command teaching style are still very low. Passing learning is complete after cycle II, this is due to the provision of motivation that triggers the enthusiasm of students to learn and changes in learning variations. Meanwhile, in cycle I, students are not familiar with the teaching methods provided by researchers, so students need to adapt to the learning methods provided by the researcher. Based on the above research results, it can be concluded that the student learning outcomes using the commando teaching method have increased from cycle I to cycle II.